Tinjauan Naratif: Efektivitas Nefroprotektif Ekstrak Black garlic (Alium Sativum L.) dalam Menurunkan Kadar Ureum - Wulandari Pramuda Wardani; Intan Adevia Rosnarita; Hasriyani Hasriyani (KOLONI, 2026)
Acute kidney injury can be triggered by gentamicin-induced nephrotoxicity due to drug accumulation in renal cortical epithelial cells, which increases reactive oxygen species (ROS) and causes oxidative stress, as reflected by elevated blood urea levels. Black garlic (Allium sativum L.) contains S-allyl cysteine (SAC), a potent antioxidant that may neutralize oxidative stress and protect the kidney. This narrative review aims to evaluate the effectiveness of black garlic extract in lowering blood urea levels across various animal models of nephrotoxicity. A literature search was conducted on PubMed, Scopus, and Google Scholar for studies published between 2020 and 2025 using the keywords "black garlic", "blood urea", and "nephroprotective". A total of 3 relevant articles meeting the inclusion criteria were analyzed in this review. The results show that administration of black garlic extract was consistently associated with reduced blood urea levels toward normal values in animal models induced by gentamicin as well as other nephrotoxic agents such as cisplatin and sodium benzoate. This blood urea reduction positively correlated with improved renal histopathology, characterized by decreased tubular necrosis and inflammatory cell infiltration. Additionally, black garlic extract increased the activity of endogenous antioxidant enzymes, including superoxide dismutase, glutathione peroxidase, and catalase, while decreasing malondialdehyde levels as a marker of lipid peroxidation. Furthermore, black garlic extract also reduced caspase-3 expression, indicating inhibition of the apoptotic pathway. In conclusion, black garlic extract demonstrates potential as a nephroprotective agent in lowering blood urea levels in various nephrotoxicity models through antioxidant, anti-inflammatory, and anti-apoptotic mechanisms.